Emerging from Darkness : Studies in the Recovery of Manichaean Sources - Mirecki, Paul; BeDuhn, Jason (Nag Hammadi and Manichaean Studies, 1997)
Modern interpretation of the Manichaean religious tradition requires a firm foundation in the sober and meticulous reconstruction of highly fragmentary sources. The studies collected in this volume contribute to such a foundation by bringing new primary texts to the public for the first time, extracting new data from previously known sources, and defining and delimiting important but previously neglected sets of material. The studies are authored by an international group of leading scholars in the fields of ancient Mediterranean and Near Eastern studies, comparative religion, early Christianity, patristics, art history, Turkic studies and Coptology. The textual and art historical materials examined possess distinctive histories, character and significance representing the broad geographical range of Manichaeism from Algeria to China. By elucidating these essential remains of the Manichaean religion, the comprehensive treatments contained in Emerging from Darkness provide a provocative picture of Manichaeism as a diverse and productive tradition in a variety of settings and media. The volume will be foundational for future scholarly studies on the sources presented and for studies in Manichaeism and late antique religions in general.